Simultaneous determination of small molecules and proteins in wastewater-based epidemiology - Picó, Yolanda; Ginebreda, Antoni; Carrascal, Montserrat; Abian, Joaquin; Barceló, Damià (Frontiers in Analytical Science, 2024)
Wastewater-based epidemiology (WBE) aims to understand a population's consumption habits, exposure to chemicals, and the prevalence of specific diseases or pathogens. This is achieved by the chemical or biological/genomic determination of biomarkers (e.g. excreted metabolic products), which are in urban wastewater generated by that population. WBE has been mostly linked to the determination of small molecules of human origin using liquid-chromatography mass spectrometry (LC-MS). In this Perspective, we provide a state-of-the-art and critical evaluation of further developments in the information achieved by determining small molecules as well as the most promising analytical techniques to enlarge the information obtained. By simultaneously monitoring small and large molecules we can comprehensively trace the population's health by their consumption of prescribed pharmaceuticals and illegal drugs, as well as by the amount of excreted macromolecule biomarkers such as peptides and proteins. Moreover, speciesspecific protein sequences allow us to monitor animal populations reflecting farming and slaughterhouse activities (poultry, pigs…) or pest occurrences (rats). To this end, the capability of proteomic studies using high-resolution tandem mass spectrometry is highlighted and compared in the context of other advances in the broader field of highresolution mass spectrometry (HRMS).